Indonesia's Attractiveness As An Investment Destination Direct Overseas Case Study Ikn Development - Mahendra Deni Antoro (Journal of Economic and Business Analysis, 2025)
Abstract: The construction of Indonesia's new capital city (IKN) is a strategic initiative to increase the country's attractiveness for foreign investment (FDI) as well as create a new economic growth center. This article discusses the driving factors, challenges, and strategies to support FDI in the development of IKN. With its strategic location and significant domestic market potential, supported by government regulations such as the Job Creation Law, Indonesia offers promising opportunities for foreign investors in priority sectors, including infrastructure and renewable energy. However, the project faces various challenges, including inadequate supporting infrastructure in East Kalimantan, bureaucratic complexity, and global economic uncertainty. Keywords: IKN; Investment; Development